Sea-Ice Retreat From the Northeast Greenland Continental Shelf Triggers a Marine Trophic Cascade - Laverick, Jack H (Global change biology, 2025)
Global Change Biology© 2025 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.